Feedback on Quranic language textbook for beginners (L2T) for Arabic-based programmes - Roslan, Muhammad Hanis; Mohd Talib, Muhammad Azamuddin; Marosadee, Abdul Hadi; Abdullah, Shamsuddin (Asian Scholars Network, 2025)
A textbook is crucial to support the teaching and learning process of a language course. In the Department of Quranic Language, a textbook has been developed and used to support the implementation of Quranic Language Level 2 Course for Arabic-based programmes. Nevertheless, there has yet to be a systematic analysis of feedback on this textbook. The lack of this analysis impedes quality improvement of the textbook. Therefore, the purpose of this paper is to probe the feedback of teachers and students on the textbook. Using mixed mode method, a questionnaire was used to gather quantitative and qualitative feedback from 10 teachers and 300 students that will be randomly sampled. The data of the feedback was analysed using statistical analysis and content analysis to determine whether the feedback is positive or negative. Results showed that the students’ and teachers’ feedback on the textbook is positive. This paper has contributed to the improvement of the textbook for future use.